Kidney Ischemia/Reperfusion Injury Induces Changes in the Drug Transporter Expression at the Blood–Brain Barrier in vivo and in vitro - Burek, Malgorzata; Burmester, Sandra; Salvador, Ellaine; Möller-Ehrlich, Kerstin; Schneider, Reinhard; Roewer, Norbert; Nagai, Michiaki; Förster, Carola Y. (Frontiers in Physiology, 2020)
Ischemia/reperfusion injury is a major cause of acute kidney injury (AKI). AKI is characterized by a sudden decrease in kidney function, systemic inflammation, oxidative stress and dysregulation of the sodium, potassium and water channels. While AKI leads to uremic encephalopathy, epidemiological studies have shown that Aki is associated with a subsequent risk for developing stroke and dementia. To get more insights into kidney-brain crosstalk, we have created an in vitro co-culture model based on human kidney cells of the proximal tubule (HK-2) and brain microvascular endothelial cells (BMEC). The HK-2 cell line was grown to confluence on 6-well plates and exposed to oxygen / glucose deprivation (OGD) for 4 hours. Control HK-2 cells were grown under normal conditions. The BMEC cell line cerebED was grown to confluence on transwells with 0.4 µm pores. The transwell filters seeded and grown to confluence with cereEND were inserted into the plates with HK-2 cells with or without OGD treatment. In addition, cerebEND were left untreated or treated with uremic toxins, indole-3- acetic acid (IAA) and indoxyl sulfate (IS).The protein and mRNA expression of selected BBB-typical influx transporters, efflux transporters, cellular receptors and tight junction proteins was measured in BMECs. To validate this in vitro model of kidney-brain interaction, we isolated brain capillaries from mice exposed to bilateral renal ischemia (30 minutes) / reperfusion injury (24 hours) and measured mRNA and protein expression as described above. Both in vitro and in vivo systems showed similar changes in the expression of drug transporters, cellular receptors and tight junction proteins. Efflux pumps in particular Abcb1b, Abcc1 and Abcg2 have shown increased expression in our model. Thus, our in vitro co-culture system can be used to study the cellular mechanism of kidney and brain crosstalk in renal ischemia / reperfusion injury.